Undergraduate Engineering Students’ Conceptual and Procedural Knowledge of Wave Phenomena - Mioković, Željka; Varvodić, Sanda; Radolić, Vanja (International Journal of Electrical and Computer Engineering Systems, 2012)
The engineering students’ education at the university level is mainly focused on procedural knowledge which includes proficiency in problem-solving and calculation whereas their conceptual knowledge, as another very important factor associated with the enhancement of engineering skills, is often insufficient. The aim of this study is to assess the undergraduate engineering students’ conceptual and procedural knowledge of wave phenomena as one of basic topics in introductory physics courses either in high school or college as well as in electronic courses at the graduate level of electrical engineering. This paper also examines the change of engineering students’ conceptual understanding in this domain prior to and after instruction in the calculus-based physics course (Physics 2) and the relation between students’ conceptual and procedural knowledge of wave phenomena. The undergraduate engineering students’ procedural knowledge was measured by assessing their performance in the final exam in the calculus-based physics course, whereas the modified Wave Concept Inventory (mod-WCI) test was designed as a multiple-choice questions test to assess their conceptual understanding of wave phenomena. The obtained results were compared with the assessment of J. J. Strossmayer University of Osijek engineering students’ conceptual understanding of electromagnetism. This assessment has been conducted recently using a well known multiple-choice test, the Conceptual Survey of Electricity and Magnetism (CSEM). The data analysis of multiple-choice questions was performed by statistical methods of classical test theory which determines reliability and discrimination of the test as well as the relation of particular questions to the entire test. Frequency distributions, normalized gain, correlations, and standardized Student’s t-test were also used in data analysis. Significant difficulties in the engineering students’ conceptual understanding of wave phenomena and some students’ misconceptions in this domain have been identified. A rather low correlation between students’ conceptual and procedural performance in the research physics domain has been recognized and confirmed.